Investigation of Surface Roughness Effects on Flow Patterns and Thermal Performance in Additively Manufactured Channels - Hollenhorst, Viola; Riese, Julia; Kenig, Eugeny Y.

Influence of the shank geometry on the joint formation of the versatile self-piercing riveting of ultra-high-strength steel-aluminium and aluminium-aluminium assemblies - Kaimann, Pia Katharina; Ritter, Nico; Bobbert, Mathias; Meschut, Gerson (Discover Mechanical Engineering)
To reduce CO₂ emissions, the automotive industry is adopting multi-material structures. Fusion-based joining reaches its limits for aluminium–steel due to brittle intermetallic phases and mismatched thermophysical properties; therefore, mechanical joining (e.g., SPR) is used. Though conventional SPR requires tool changes for different stack-ups. Versatile self-piercing riveting (V-SPR) addresses this with an extended punch actuator and a multi-range-capable rivet (Kappe in PERD16:363–378, 2022), enabling joints up to 600 MPa across varying thicknesses without retooling. With the use of ultra-high-strength steels up to 1000 MPa, optimisation is required. This study quantifies how rivet shank geometry affects joint formation using a design of experiments and validated 2D axisymmetric FE simulations. The optimum depends strongly on the material system. For CP1000–EN AW-6014, maximum interlock f is predicted for a medium shank thickness of about 0.73 mm, a small internal foot radius of 0.620 mm, and a deeper drill depth of 3.136 mm, yielding f fc =0.4503 mm with a desirability of 0.954. For EN AW-6014–EN AW-6014, the optimum shifts to a thinner shank of 0.670 mm, a larger internal foot radius of 0.820 mm and a shallow drill depth of 2.30 mm, giving ffc = 0.3023 mm with a desirability of 1.0. A compromise geometry of 0.713 mm shank thickness, 0.776 mm internal foot radius and 2.755 mm drill depth achieves ffc = 0.3641 mm for CP1000–aluminium and ffc = 0.1851 mm for aluminium–aluminium with an overall desirability D = 0.6378, expanding V-SPR to ultra-high-strength steel–aluminium joints while maintaining aluminium joinability.

Improving the load-bearing capacity of clinched joints through cavity filling with structural epoxy adhesive. - Devulapally, Deekshith Reddy; Tröster, Thomas (Discover Mechanical Engineering)

Identification of multiple steady states in reactive absorption columns equipped with structured packings - Franke, Patrick; Lutters, Nicole; Riese, Julia; Kenig, Eugeny

A gradient-damage model for amorphous glassy polymers: Consistent formulation of viscoplasticity and damage evolution in a micromorphic framework - Hamdoun, Ayoub; Mahnken, Rolf; Ostwald, Richard (European Journal of Mechanics / A Solids)

Untersuchung der Einflussfaktoren auf die Recyclingfähigkeit von flammgeschütztem Polyamid 12-Pulver beim selektiven Lasersintern (Studienarbeit) - Hüwel, Fabian

Simulation-based process chain for aluminum clinched joints: Predicting geometry, strength, and failure behavior - Mergheim, Julia; Wallmersperger, Thomas; Wolf, Eugen; Schlichter, Malte; Ludwig, Jean-Patrick; Friedlein, Johannes; Gerritzen, Johannes; Devulapally, Deekshith Reddy; Chen, Chin; Weiss, Deborah; Krome, Sven; Reschke, Gregor; et al. (Journal of Advanced Joining Processes)

Single-surface and double-surface plasticity for micropolar continuum - Börger, Alexander; Mahnken, Rolf (Archive of Applied Mechanics)
Abstract The micropolar continuum is a special case of a micromorphic material model and has additional degrees of freedom in the form of microrotations compared to the classical continuum. With the micropolar model, size effects can be considered and the boundary value problem can be regularized when localization effects occur. In order to map the microrotations, an additional strain measure and an additional stress are introduced. For simulation of plasticity, it is possible to define one yield function, and thus one plastic multiplier as well as one equivalent plastic strain occur. This approach is known as the single-surface plasticity approach. The macro- and micro-stresses are coupled in a common flow function. On the other hand, there is the so-called double-surface plasticity when one yield function, one plastic multiplier, and one equivalent plastic strain, respectively, are introduced for each of the macro- and micro-variables. The coupling of the macro- and micro-variables is established by a possible coupling of both yield functions. The purpose of this paper is to compare both approaches and to identify similarities and differences.

ML-based Prediction Framework for varying Traffic Signal Control Strategies and its GLOSA-application - Malena, Kevin; Link, Christopher; Gausemeier, Sandra; Trächtler, Ansgar (2025 IEEE 28th International Conference on Intelligent Transportation Systems (ITSC))
This paper deals with the development and results of a prediction framework for traffic light control systems as well as the usage and benefits of such predictions in green light optimal speed advisory (GLOSA) scenarios. Various machine learning methods like support vector machines, neural networks or reinforcement learning were evaluated for their applicability in the prediction context and compared based on their efficiency and most importantly accuracy. The resulting prediction framework uses decision tree ensemble models combined with certain model knowledge to forecast different control strategies. This method was chosen due to its best performance in various test scenarios. Very high accuracy and fidelity were achieved for standard control methods like fixed-time, time-of-day-based and 'ordinary' traffic-based programs. Only for the more sophisticated model predictive control which was tested lower accuracies were achieved. For the upcoming GLOSA application the penetration of equipped vehicles was varied for different traffic scenarios and control strategies. Results showcase high potentials for enhancing urban mobility and reducing environmental impact by lower emissions and waiting times. However, it is also clear from the studies presented in this contribution that the coordination of the control strategy with the GLOSA vehicles is of enormous importance.
Keywords: ML; Prediction; Tree Ensembles; GLOSA

Response surface methodology for parameter development of alloy UNS N09946 processed with laser powder bed fusion - Wooldridge, Madison; Holzweissig, Martin; Hoyer, Kay-Peter; Schaper, Mirko (Rapid Prototyping Journal)
Purpose The adoption of laser powder bed fusion (LPBF) as an additive manufacturing technique has been slow in the oil and gas (O&G) industry because of the uncertainty regarding material performance and the lack of suitable materials. The high investment and time required for LPBF development also discourage adoption. This study aims to address these concerns by developing a parameter set for a relevant material using a systematic approach to optimize the density of the printed parts with reduced experimental effort. Design/methodology/approach First, an industry-relevant Ni-based superalloy, UNS N09946, was gas-atomized to produce a powder. The powder was fully characterized to ensure successful printing. Next, a processing parameter set tailored for achieving full density was developed for UNS N09946 using a Design of Experiments (DoE) approach based on the volumetric energy density equation. Findings A model was created using Response Surface Methodology that relates laser power, scan speed and hatch distance to efficiently identify successful parameter combinations, thus reducing the number of specimens necessary for the successful manufacturing of UNS N09946 using LPBF. A part density of 99.9% was achieved using this method. Originality/value This study applies an existing experimental design method to a never-before-printed material. The reduced experimental effort through this method and lessons learned from the gas atomization process can be directly applied to other materials in and outside the O&G industry to further the adoption of LPBF as a serious manufacturing technology.

A Numerical Study on the Mutual Influence of Joint Orientation and Component Geometry in Non-Rotationally Symmetric Clinched Joints - Devulapally, Deekshith Reddy; Tröster, Thomas (Materials Science Forum)
Clinched joints with non-rotationally symmetric geometries exhibit orientation-dependent mechanical behavior that is commonly neglected in structural-scale simulations. Reuleaux triangle shaped clinched joints, in particular, show pronounced in-plane anisotropy depending on their orientation. While such effects have been studied at joint and specimen scale, their relevance at the structural level remains largely unexplored. In this work, the influence of joint orientation on the bending response of a joined structure is investigated using numerical simulations. A simplified joint replacement model based on the *CONSTRAINED_SPR2 point-connector formulation in LS-DYNA is employed, with parameters calibrated from previously obtained experimental force displacement data. A hat shaped profile structure subjected to three-point bending is analyzed in a parametric study considering variations in joint orientation, joint spacing, and profile geometry. The results show that joint orientation has little influence during the initial deformation phase but becomes increasingly significant at larger displacements, where joint behavior governs load transfer. Orientation dependent effects are found to influence the global force displacement response and local load redistribution among joints, with magnitudes comparable to those induced by changes in joint spacing and structural geometry. The findings confirm that joint orientation effects remain relevant at the structural level and should be considered in the design of structures assembled using non-rotationally symmetric clinched joints.

Einfluss von Misch-, Material- und Prozessparametern auf die Koaleszenz flammgeschützter Pulver im Lasersintern - Peitz, Robin

Fiber-matrix adhesion in glass fiber reinforced thermoplastic composite laminates and its effect on mechanical properties - Moritzer, Elmar; Brandes, Philipp; Wittler, Maurice; Claes, Leander; Wippermann, Mareen; Haag, Markus; Gries, Thomas; Henning, Bernd (International Polymer Processing)
With the growing demand for lightweight solutions to reduce emissions, especially in the transportation, automotive and aerospace sectors, recyclable, continuous fiber-reinforced plastic composite laminates with a thermoplastic matrix are of rising interest. To achieve their maximum mechanical properties, the fiber-matrix adhesion (FMA) is critical. In this work, continuous fiber-reinforced thermoplastic laminates (CFRTPL) with a polypropylene (PP) matrix and twill woven glass fiber fabrics are produced by film stacking. The films used contain different amounts of maleic-anhydride-grafted PP (MA-g-PP) as a coupling agent to produce CFRTPL of different mechanical strengths. To analyze the FMA, the CFRTPL are subjected to Charpy-impact and tensile tests. Additionally, single fiber pull-out tests (SFPT) are conducted to further investigate the effect of MA-g-PP on the FMA. The results of the SFPT show an improvement in apparent interfacial shear strength (AIFSS) when the MA-g-PP content is increased, which can be attributed to an increase in FMA. However, the research shows that MA-g-PP has a low impact on the mechanical properties if the force is applied parallel to the warp and weft threads during tensile testing and the results of the Charpy-impact testing suffer from embrittlement of the matrix material. Subsequently, the results of this study are compared to three-point flexural tests conducted in a previous study. It can be concluded that tensile and impact tests are not suited to investigate FMA on a macroscopic scale, while SFPT and flexural tests provide a better alternative.

Opportunities and obstacles for industrial applications - Schlüter, Alexander; Krogbäumker, Luisa; Böse, Kevin; Riese, Julia (Hydrogen and Bioenergy)

Life prediction of adhesive steel joints under ageing stress – experimentally based model validation - Damm, Jannis; Ummenhofer, Thomas; Albiez, Matthias; Meschut, Gerson; Sander, Sascha; Teutenberg, Dominik; Kötz, Fabian (The Journal of Adhesion)

Matching Heat Pump Configurations and Process Parameters for Cost‐Minimal Heat‐Integrated CO2-Capturing Process - Wloch, Johannes; Grünewald, Marcus; Riese, Julia (Chemie Ingenieur Technik)
ABSTRACT The integration of heat pumps offers a promising route for electrifying chemical processes and reducing CO 2 emissions. Their feasibility strongly depends on the temperature levels and the quantities of available heat sources and sinks, which can be influenced by adjusting process operating parameters to enhance integration potential. The number and quality of these sources and sinks also determine suitable heat pump configurations and therefore the technical and economic viability of implementation. In addition, refrigerant selection is a critical factor, as it is restricted by regulations such as the F‐Gas Regulation. This study investigates how different operating parameters affect the integration potential of various heat pump configurations in a CO 2 absorption process using MEA as solvent. Furthermore, economic evaluations are carried out considering different electricity price scenarios and allowable refrigerants.

A verification-stability-validation framework for optimal hyperelastic modeling of rubber-like materials - Houari, Fadoua; Caylak, Ismail; Ostwald, Richard (Mechanics of Materials)

Experimental investigation of local joining element kinematics in mechanical joints and surrogate modelling for crash applications - Bähr, Philipp; Striewe, Marius; Dargel, Alrik; Sommer, Silke; Hein, David; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
Subject of this paper is the investigation of the influence of local joint kinematics on the load-bearing and failure behavior of self- piercing riveted (SPR) joints. It can be shown that the local joint kinematics of SPR joints correlate with the failure mechanism of the joint. The kinematics are highly influenced by the material properties of the joining partners. Detailed experimental results from tensile tests on a representative SPR joint are presented, with local joint kinematics quantified using multiple complementary measurement methods (optical measurement, micrographs, in situ computer tomography). Furthermore, results of component tests are shown where the kinematics of the joints have been measured in the same manner. The experimental results are later used to calibrate simulation models for crash application which are used to simulate the specimen and component tests. The results of the investigation show that the local joint kinematic influences the failure behavior of the joint. Simulations of the experimental tests have shown good results, and the investigated models are able to predict the actual joint behavior.

Metadata Model for Engineering of Sustainable Products in Value Creation Networks - Gräßler, Iris; Rarbach, Sven; Pottebaum, Jens; Luessen, Florian; Hoffmann, Joerg (Procedia CIRP)

Metadata-based assessment of Data Quality for Engineering of Sustainable Products - Gräßler, Iris; Rarbach, Sven; Pottebaum, Jens; Hoffmann, Joerg (Procedia CIRP)